The role of vascular function on exercise capacity in health and disease. (3rd March 2020) - Poole, David C.; Behnke, Brad J.; Musch, Timothy I.
Abstract: Three sentinel parameters of aerobic performance are the maximal oxygen uptake ( V ̇ O 2 max ), critical power (CP) and speed of the V ̇ O 2 kinetics following exercise onset. Of these, the latter is, perhaps, the cardinal test of integrated function along the O2 transport pathway from lungs to skeletal muscle mitochondria. Fast V ̇ O 2 kinetics demands that the cardiovascular system distributes exercise‐induced blood flow elevations among and within those vascular beds subserving the contracting muscle(s). Ideally, this process must occur at least as rapidly as mitochondrial metabolism elevates V ̇ O 2 . Chronic disease and ageing create an O2 delivery (i.e. blood flow × arterial [O2 ], Q ̇ O 2 ) dependency that slows V ̇ O 2 kinetics, decreasing CP and V ̇ O 2 max, increasing the O2 deficit and sowing the seeds of exercise intolerance. Exercise training, in contrast, does the opposite. Within the context of these three parameters (see Graphical Abstract), this brief review examines the training‐induced plasticity of key elements in the O2 transport pathway. It asks how structural and functional vascular adaptations accelerate and redistribute muscle Q ̇ O 2 and thus defend microvascular O2 partial pressures and capillary blood–myocyte O2 diffusion across a ∼100‐fold range of muscle V ̇ O 2 values. Recent discoveries, especially in the muscle microcirculation and Q ̇ O 2 ‐to‐ V ̇ O 2 heterogeneity, are integrated with the O2 transport pathway to appreciate how local and systemic vascular control helps defend V ̇ O 2 kinetics and determine CP and V ̇ O 2 max in health and how vascular dysfunction in disease predicates exercise intolerance. Finally, the latest evidence that nitrate supplementation improves vascular and therefore aerobic function in health and disease is presented. Abstract : Abstract figure legend Three sentinel parameters of aerobic performance are the O2 uptake ( V ̇ O 2 ) kinetics following the onset of exercise, critical power (CP) or critical speed (CS) (asymptote of the power/speed–time relation for high intensity exercise) and the maximal O2 uptake ( V ̇ O 2 max ). The dependence of each parameter on O2 delivery is highly subject, exercise mode and context dependent. That said, for upright rhythmic cycling or running exercise the boxes apportion the relative importance of cardiac, vascular and mitochondrial O2 delivery/utilization to each in the untrained state (pre‐) and the participation of each in the training adaptation (post‐) for each parameter. This brief review explores that dependency in health and disease utilizing exercise training and other conditions such as nitrate supplementation to unveil how vascular function and dysfunction predicate exercise tolerance and intolerance within the scope of these three parameters of aerobic function.